Preschool Teachers and Preservice Teachers’ Verbal Problem Posing Skills Related to Addition and Subtraction - Yaşare Aktaş Arnas; Kamuran Tarım (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The aim ofthis study is to examine preschoolteachers’ and pre-service teachers’ verbal problem-posingskills. The data of the study was gathered from 179 third and fourth yearstudents studying in the preschool teaching department in a public universityin Adana in the 2016-2017 academic yearand 93 preschool teachers working in pre-school education institutionsaffiliated to Provincial Directorate of National Education in Adana. The dataof the study was collected by using Verbal Problem Posing Form created by theresearchers. Frequency and percentage techniques were used to analyze the data.As a result of the study, it was seen that teachers and pre-service teachers were able to pose someverbal problem types correctly while they could not pose other types. Amajority of both teachers and pre-serviceteachers were largely successful in posing joining / result unknown; joining /change unknown; separating / result unknown and separating / change unknownproblem types. Furthermore, both teachers and pre-service teachers had very little success in posingpart-part-whole / whole unknown; part-part-whole / part unknown; comparison / smallerunknown; comparison / difference unknown problem types. Additionally, amajority of participants were found to be unsuccessful in posing thecomparison/larger unknown type of problems.